A Multi-Criteria Solution Approach for UAV Engine Selection in Terms of Technical Specification - Ucar, Ukbe; Adem, Aylin; Tanyerı, Burak (My University, 2022)
Unmanned Aerial Vehicles (UAVs) are electronic systems that are used extensively in every field today and that develop and change very quickly with technology. UAVs are used extensively in many areas, especially in logistics processes, search and rescue activities, military operations, fight to forest fires, photography, monitoring and inspection of agricultural processes. Furthermore, considering their hobby use, it is understood that UAVs have a large commercial market and a high economic value. UAV systems contain many electronic and mechanical systems and many performance criteria can be found for UAV systems. The main ones of these performances are stabilization and engine power. The most important system affecting these performance criteria is the engine. In this study, engine alternatives available in the market for UAVs with take-off weights of 750 to 800 grams were evaluated in terms of mechanical and physical criteria of engine systems, and as a result, the ideal engine model was determined by Analytic Hierarchy Process (AHP) for maximum stabilization and velocity purposes. The article is the first in the literature in terms of the problem obtained and the application of the AHP method to this problem. Thanks to the study, it is aimed to create a Decision Support System for both UAV manufacturers and UAV users so that they can choose the ideal models in engine selection processes
Keywords: Mühendislik; Deniz; Mühendislik; Makine; Matematik; Robotik